Ethics and Peaceful Conduct towards the Followers of Denominations - Razieh Aliakbari (اخلاق وحیانی)
The present paper entitled “Ethics and Peaceful Conduct towards the Followers of Denominations” seeks to demonstrate the Shiites’ desirable way of conduct towards the followers of other Islamic denominations. To this end, the contents of this article have been divided into two sections of “Moral Dilemmas” and “Moral Values” in the way of conduct towards the followers of other denominations. In the first section, i.e. the Moral Dilemmas, the ethical “don’ts” and blameworthy behaviors have been addressed and in the second section the moral values which must be observed in one’s behavior towards the followers of other denominations have been studied. Observing ethics in one’s conduct towards other Muslims is, in effect, in line with the instructions of the Quran with regard to unity among Muslims (واعتصموا بحبل الله جمیعا و لا تفرقوا) and also the theory of the Approximation of the Islamic Denominations, for, in the author’s opinion, the only removable obstacle to the solidarity of the followers of all of the Islamic denominations is the lack of adherence to Islamic ethics. Hence, if a clear distinction is made between the ideological differences and ethical behavior and conduct with Muslims, then religious differences would not be a barrier to observing ethics and treating Muslims peacefully. Thus, this study intends to demonstrate the fact that, despite all of their disagreements and differences in their religious attitudes, the followers of all Islamic denominations can achieve approximation and a peaceful life based on their common ethical standards taught by the honorable Messenger of Allah (peace be upon him and his household) for the perfection of which he was delegated as a Prophet.